But, Teacher, I Don't Like to Read, Or How To Make Reading Alluring - DiSibio, Robert A.; Savitz, Fred R. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
The domino effect of illiteracy can be halted if students are given opportunity early in life to develop a positive attitude toward reading. Research supports the notion that reading interests lead to knowledge, which leads, in turn, to increased comprehension. Motivational ideas include using trade books and literature as collateral material in content area reading, putting a book on trial with students indicting and defending a story, broadcasting a book review on the school public address system, and providing a list of items for students to locate in a local newspaper. Several successful reading programs in schools across the country provide interesting reading materials and facilitate discussion groups and other reading activities. Reading attitudes prevalent in the home environment have great influence on the children's attitudes, but the major responsibility still rests with teachers, who must represent models of positive reading habits. (Several teaching ideas are appended.) (HTH)
ERIC Note: Paper presented at the Annual Meeting of the New York State Reading Association (17th, Kiamesha Lake, NY, November 8-13, 1983).
Educational level discussed: Elementary Secondary Education.
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Attitude Change; Content Area Reading; Elementary Secondary Education; Literacy; Motivation Techniques; Reading Attitudes; Reading Comprehension; Reading Habits; Reading Instruction; Reading Interests; Reading Materials; Reading Programs; Reading Research; Teaching Methods; Guides, Classroom -- Teacher; Speeches/Meeting Papers